Child-Friendly Justice Before, During and After Completion of Judicial Proceedings in the Guidelines of the Committee of Ministers of the Council of Europe on Child-Friendly Justice - Vujić, Nenad; Stevanović, Ivana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
In the paper, the authors analyse the concept of "child-friendly justice": before, during and after the completion of judicial proceedings in a way defined by the Guidelines of the Committee of Ministers of the Council of Europe on Child-friendly Justice. Considered and analysed are issues of paramount importance for the part of the Serbian negotiation process regarding the opening of certain negotiating chapters, while keeping in mind issues for the promotion and protection of child rights defined by the Draft Action Plan for Chapter 23 of the Republic of Serbia. The aforementioned is followed by the main aim of this work, a review and analysis of the newly established European standards for the promotion and protection of the rights of the child in the area of justice, observed also from the point of view of the practice of the European Court of Human Rights in Strasbourg.